IFCC Working Group Recommendations for Assessing Commutability Part 2: Using the Difference in Bias between a Reference Material and Clinical Samples. (1st March 2018) - Nilsson, Göran; Budd, Jeffrey R; Greenberg, Neil; Delatour, Vincent; Rej, Robert; Panteghini, Mauro; Ceriotti, Ferruccio; Schimmel, Heinz; Weykamp, Cas; Keller, Thomas; Camara, Johanna E; Burns, Chris; et al.
Abstract: A process is described to assess the commutability of a reference material (RM) intended for use as a calibrator, trueness control, or external quality assessment sample based on the difference in bias between an RM and clinical samples (CSs) measured using 2 different measurement procedures (MPs). This difference in bias is compared with a criterion based on a medically relevant difference between an RM and CS results to make a conclusion regarding commutability. When more than 2 MPs are included, the commutability is assessed pairwise for all combinations of 2 MPs. This approach allows the same criterion to be used for all combinations of MPs included in the assessment. The assessment is based on an error model that allows estimation of various random and systematic sources of error, including those from sample-specific effects of interfering substances. An advantage of this approach is that the difference in bias between an RM and the average bias of CSs at the concentration (i.e., amount of substance present or quantity value) of the RM is determined and its uncertainty estimated. An RM is considered fit for purpose for those MPs for which commutability is demonstrated.